Implementation of Maqāṣid Sharī’ah in Reform of Case Management of Violence against Women and Children - Aibak, Kutbuddin (Shariah Faculty UIN Maulana Malik Ibrahim Malang, 2023)
This study aims to reflect on the values of maqāṣid sharī’ah in management patterns of violence cases against women and children. This is based on arguments about case management which until now has not been able to completely resolve violence against women and children in Indonesia. The presence of maqāṣid sharī’ah in the management pattern of violence against women and children is expected to hold strong legitimacy to formulate a management pattern that is integrated with the basis and values of Islamic law goals. This step is a form of embodiment to resolve violence cases against women and children through maqāṣid sharī’ah-based case management to reflect the resolution of violence cases through integrated steps to realize solutive fiqh for the matter. In an academic purview, this study uses a literature review involving primary and secondary data observed with in-depth analysis. The findings in this study indicate that maqāṣid sharī’ah has implications for the realization of protection for women and children through case management reforms.